HUBUNGAN DUKUNGAN SOSIAL KELUARGA DENGAN PEMBERIAN ASI EKSKLUSIF PADA BAYI USIA 0-6 BULAN - Sumy Dwi Antono; Eny Sendra; Lidya Putri Kartika Dewi (coba, 2019)
Abstract: Family social support is an effort given to others, both moral and material to motivate the person in carrying out activities. Support or support from other people or people nearby is very important in the success or failure of breastfeeding. Coverage of Checked Babies and Exclusive Breastfeeding with the lowest coverage in 2017 is lowest in the Wonorejo Health Center (33.3%). The purpose of this study was to determine the relationship of family social support with exclusive breastfeeding for infants aged 0-6 months. The research method is descriptive analytic with a retrospective approach. The samples in this study were 34 samples. Sampling in this study uses Simple Random Sampling. The result of bevariate analysis used Fisher Exact test with error level on Fisher Exact α value of 0.05 where ρ value = 0.002. From the result of 0.002 <0.05, H0 is rejected by H1 so that it can be concluded that there is a relationship between family social support and exclusive breastfeeding for infants aged 0-6 months in the village of Rembang, the working area of ​​the Wonorejo health center in Kediri regency. Based on these results, it is expected to increase health promotion efforts, especially regarding intensive exclusive breastfeeding through direct communication to the community by involving families